NORA’S CHARACTERDEVELOPMENT AFTER APPARENT DEATH IN MATT HAIG’S THE MIDNIGHT LIBRARY: character development, apparent death, character - Juang Galuh Ratu Praditha; Danu Wahyono (Fakultas Sastra Universitas Gresik, 2021)
This study aims to analyze the development of Nora’s character after the apparent death in Matt Haig’s the Midnight Library. The data of this study is taken from the words and dialogues in Matt Haig’s the Midnight Library that shows the characters and character development of the main character, Nora. The writer uses psychological approach and focuses on apparent death because she wants to analyze character development happens to Nora after apparent death. The result of the analysis, first the character of Nora easy to dispirited, negative thinking, pessimist, ungrateful, and always blame on herself for everything happens. the second is apparent death in Midnight Library influences Nora’s character. The third, the writer finds the character development in Nora that she becomes happier, positive thinking, always grateful, optimistic, and always assumes everything that happens in life is a good lessons for life.